Inclusive or engaging (‘absorbing’) education: interpretations of social constructs in the context of change in education - Ališauskienė, Stefanija; Miltenienė , Lina (Special Education, 2018)
Lithuania, like other European countries, has committed to develop and implement inclusive education systems. The ideology of inclusive education must be closely linked with proper and  appropriately  agreed  terminology and concepts. Based on the paradigm of  social  constructivism,  discussions and debates among representatives of various related structures, systems and areas both in the international and national context enable to construct social constructs with reconciled and comparable content. Otherwise, new concepts simply replace the old ones but do not change either policy or practice. In various social cultural contexts, such concepts as integration, integrated education, inclusion, inclusive education, school for all, quality education for all can be interpreted differently. This article aims to reveal the concept of inclusive education and how the content of this concept is reflected in the latest national legal documents. The article is based on the study of theoretical sources, the review of international documents related to entrenchment of human rights and inclusive education approaches, and the analysis of national education and training documents. Six documents – The National School. The Concept of Secondary General Education School of Lithuania (1989); Law on Education of the Republic of Lithuania (1991; 2011); Law on Special Education of the Republic of Lithuania (1998); The National Strategy on Education for the years 2013- 2022; The Concept of the Good School (2015) – were analysed in the following aspects: essential approaches of the education system, aims of education and regulation of educational assistance. Analysing the above-mentioned aspects, their coherence with inclusive education approaches was sought. Besides, analysing selected documents, the concepts “integrated education/integration”, “inclusive education/inclusion”, “engaging (absorbing) education” and their explanations were sought.Educational change towards inclusive education highlighted the need to change established traditions, values and concepts of education and training. Change in education and training traditions began with the approach of implementation of integrated education, emphasizing regulation of integration (engagement, absorbing) of children with special needs in mainstream schools and of concepts “partial integration”, “full integration” cohering with this approach. International systemic change in the education policy, culture and practice towards inclusive education, emphasizing quality education for all, acknowledging and appreciating the diversity of (self-)educational process participants and their needs, highlighted the importance of not only engaging (absorbing) learners in the mainstream education system but also of ensuring their participation and recognition of their achievements.The document analysis has  demonstrated  that  the  essential  approaches of inclusive education are directly or latently emphasized in the strategic documents of education of Lithuania. However, in the most recent documents on education, the concept of inclusive education is not mentioned; its content is not defined. In recent years, it is attempted to find a Lithuanian equivalent for the complex social construct “inclusive education” and to replace it with the concept “engaging education”, the content of  which  is  also  not revealed. Undefined content of complex concepts-constructs promotes various interpretations, leads to confusion of concepts (such as “integrated”/“engaged”, “inclusive” education), and impedes communication. The analysis of the most important documents regulating the country’s education has shown that most of them emphasize such educational principles as fostering of humanistic national and world cultural values, development of democratic relations, fostering of the country’s cultural traditions, preservation of national identity, etc. However, the mentioned above principlesarelargelydeclarativethoughinclusiveeducationideascanbemoreor less recognized in them. In this context, the systemic approach, methodological consistency of approaches, their clear links to the paradigm, concepts of education and training and their content are also important. Thus, “engaging” or “inclusive” education? To answer this question, to decide and agree what is what, we should rethink the content of concepts and links with the model of education and training, which we intend to implement – of integrated (engaging / absorbing) or inclusive education, clearly define them in national education documents, not confusing between the two of them.
Keywords: none